A Multithreaded Initial Detailed Routing Algorithm Considering Global Routing Guides - Sun, Fan-Keng; Chen, Hao; Chen, Ching-Yu; Hsu, Chen-Hao; Chang, Yao-Wen (2018 IEEE/ACM International Conference on Computer-Aided Design (ICCAD), 2018)
Detailed routing is the most complicated and time-consuming stage in VLSI design and has become a critical process for advanced node enablement. To handle the high complexity of modern detailed routing, initial detailed routing is often employed to minimize design-rule violations to facilitate final detailed routing, even though it is still not violation-free after initial routing. This paper presents a novel initial detailed routing algorithm to consider industrial design-rule constraints and optimize the total wirelength and via count. Our algorithm consists of three major stages: (1) an effective pin-access point generation method to identify valid points to model a complex pin shape, (2) a via-aware track assignment method to minimize the overlaps between assigned wire segments, and (3) a detailed routing algorithm with a novel negotiation-based rip-up and re-route scheme that enables multithreading and honors global routing information while minimizing design-rule violations. Experimental results show that our router outperforms all the winning teams of the 2018 ACM ISPD Initial Detailed Routing Contest, where the top-3 routers result in 23%, 52%, and 1224% higher costs than ours.